Severe outbreaks of strawberry crown and root rot caused by Macrophomina phaseolina in Tucumán, Argentina - Viejobueno, Josefina (2017)
Tucumán province is one of the most important strawberries growers in Argentina. The charcoal rot is a soilborne disease caused by the fungus Macrophomina phaseolina. This disease is spread worldwide and M. phaseolina one of the most economically important fungal pathogens. The objective of this study was to determine the susceptibility of different strawberry cultivars to M. phaseolina under field conditions. The evaluation was carried out at INTA-Famaillá in Tucumán, Argentina. Fresh-dug strawberry plants form cultivars ?Macarena?, ?Treasure?, ?Pájaro?, ?Ruby Gem?, ?Carmela?, ?Camino Real?, ?Albion?, ?Ventana?, ?Camarosa? and ?Palomar? were evaluated. All evaluated plants showed decline and death but the pathogens isolated differed among cultivars. Fusarium oxysporum was co-isolated with M. phaseolina in ?Camarosa?, ?Camino Real?, ?Albion?, ?Carmela?, ?Treasure? and ?Pájaro?. Pure isolates of M. phaseolina were obtained from ?Ruby Gem? and ?Macarena?. Pure isolates of Fusarium spp. were obtained from ?Palomar?. Plant losses and disease ratings due to M. phaseolina were greater for ?Macarena?, ?Treasure? and ?Pajaro?, followed by, ?Ruby Gem? and ?Carmela? than for ?Palomar? and ?Camarosa?, which appeared to be more tolerant to plant decline. This study demonstrates differential tolerance to M. phaseolina of currently available strawberry cultivars in Tucumán, Argentina.